Development of a module to successfully implement competency-based medical education program in an institute - Saurabh Rambiharilal Shrivastava; Prateek Saurabh Shrivastava; Jegadeesh Ramasamy (Wolters Kluwer Medknow Publications, 2018)
Medical education aims to train students in such a way that they are empowered to meet the health needs of the population. Competency-based medical education (CBME) aims to ensure that the student acquires the desired competencies to meet the needs of people in a community and even addresses the constraints attributed to the conventional medical education. Institutes with an active CBME program in place, but in novice stages, have an immense need to sensitize the faculty or the postgraduate students about the different domains of CBME. Having a module, which is designed in a systematic and structured manner, can prove to be a wonderful tool to carry out the sensitization session. The overall process of preparation of a module goes through the stages of needs assessment, designing of the module, and finally the development of a module. To conclude, the presence of a structured module built on the comprehensive needs assessment can help an institute to successfully implement CBME within their setup.